Learning in higher education while being at war - Francesca TORLONE; Anna ISHCHENKO (Revista de Știinţe Educaţiei, 2024)
Learning in higher education while being at war is the topic of this paper. The investigation on the management of one’s own learning processes by students living war conditions has been addressed through a survey that was conducted on a sample of 1,685 students at the Igor Sikorsky Kyiv Polytechnic Institute in Kiev during February-March 2023, one year after the Russian invasion. The aim is to understand the strategies adopted by students to oppose and counteract the informal learning processes that are produced by the war. Findings of the study show that, although people are immersed in adverse conditions, they can autonomously direct their own learning processes and defend themselves against the learning valencies of the war to counteract its effects. This is a possibility that might depend on the educational quality of social relations and the networks each student has and was able to build. The possibility to be trained represents the most common concern among students. It is more widespread than the precariousness of material living conditions. However, this attitude is not generalised. According to the authors, the different positions expressed by the students could be attributed to the different level of the capacity each student developed to control the learning processes they are exposed to in their daily life. Based on this capacity of control of their own informal learning processes it is possible to activate autonomous self-directed learning and tackle the challenges the war poses.